ANALISIS PENINGKATAN MUTU DAN RELEVANSI, PEMERATAAN, EFISIENSI INTERNAL PENDIDIKAN DI KABUPATEN KLATEN - Soebandriyo Soebandriyo (JURNAL LITBANG PROVINSI JAWA TENGAH, 2013)
Descriptive nature of qualitative research with the aim of the study 1. To find out the distribution of education, 2. To find an increase in the quality and relevance of education, 3. Results of research to determine the internal efficiency of education. Development of Education in terms of educational equity can be explained by several indicators such as number Partisipai Rough (GER), Pure's participation rate (NER), Ratio of Education, and the percentage of the transition rate. Based on the existing APK APK apparently highest in SD / MI is 123.01 percent and the lowest at the high school level + MA is 75.27 percent, while for the junior level at 95.37 percent + MTs. Based quality indicators, namely the coarse input rate (MCA) SD / MI by 90.27 percent, to repeat the numbers, it turns out the biggest repeat numbers found on the SD / MI is 3.88 junior / MTs of 0.14 and SM + MA is equal to 0.15. The next largest dropout rate contained in the MA + SM rate by 0.84 percent and the lowest in SD / MI in the amount of 0.06 per cent followed by 0.20 percent junior. For the primary level to the level of SM using the same indicators between the internal efficiency of education. Indicators may include the number of outputs, number of students, number of dropouts, the number of repeats, length of study, students wasted years, the ratio of inputs per input and output and input, it is known that the amount of output that is best approached in terms of the number 1000 is on the high school level + MA greatest value that is equal to 997, and the smallest are in the junior secondary vocational school for 956 + MTS was 996, while for the MI + SD of 986.